2002
DOI: 10.1200/jco.2002.20.2.503
|View full text |Cite
|
Sign up to set email alerts
|

When the Treatment Goal Is Not Cure: Are Cancer Patients Equipped to Make Informed Decisions?

Abstract: Most patients were well informed, but important gaps remain, especially concerning information about prognosis and alternatives to anticancer treatment. These gaps invite the question concerning whether patients are led toward anticancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(123 citation statements)
references
References 45 publications
3
109
0
10
Order By: Relevance
“…Oncologists do discuss the goals of systemic therapy with advanced cancer patients, as well as its impact on prognosis and side effects. However, in an analysis of 118 audio-taped oncology consultations with advanced cancer patients, fewer oncologists discuss life expectancy, the patient's treatment preference and alternatives, such as supportive care alone (Gattellari et al, 2002). The impact of treatment on patient's quality of life was discussed in only onethird of consultations, and oncologists checked for patient understanding of information in only 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Oncologists do discuss the goals of systemic therapy with advanced cancer patients, as well as its impact on prognosis and side effects. However, in an analysis of 118 audio-taped oncology consultations with advanced cancer patients, fewer oncologists discuss life expectancy, the patient's treatment preference and alternatives, such as supportive care alone (Gattellari et al, 2002). The impact of treatment on patient's quality of life was discussed in only onethird of consultations, and oncologists checked for patient understanding of information in only 10%.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that may help correct misperceptions include: having family members present at meetings with doctors to ask additional questions and record information; explaining treatment options and treatmentrelated mortality and outcome estimates a number of times (either through the use of educational materials, particularly interactive educational materials such as CD-ROMs, or through repeat visits with health care personnel and reiteration of estimates); testing patient understanding of these estimates, to verify that informed consent truly has been given; and early involvement of psychiatry and social services, when appropriate. [49][50][51][52][53][54] …”
Section: Discussionmentioning
confidence: 99%
“…Braddock et al (1999) analysed 1057 consultations of primary care physicians and surgeons in 1993 and found that only 11.3% included discussion of alternative treatment options and just 7.8% included pros and cons. An Australian study in 2001 of consultations with advanced cancer patients showed that only 27% of patients were offered a choice, and 44% were given information on an alternative course of action to anticancer therapy (Gattellari et al, 2002). In a Dutch study of advanced cancer patient care, acknowledgement of the medical oncology options of palliative chemotherapy or watchful waiting occurred in half of the consultations, with just 27% receiving extensive explanation of the watchful waiting option (Koedoot et al, 2004).…”
Section: Discrepancy Between Reported Comfort Levels and Usual Practisementioning
confidence: 99%